Lightness Compression and Hue Changes - Moreira, Humberto; Lillo, Julio (The Spanish Journal of Psychology, 2006)
Two experiments were performed to relate the Bezold-Brücke (B-B) and lightness compression effects. The first used a calibrated screen to present an achromatic luminance staircase. In addition, it reproduced, the methodology and the essential aspects the lightness compression effect discovered by Cataliotti and Gilchrist (1995). That is, observers perceived a truncated grey scale (from white to medium grey) when the staircase was the only stimulation in the near background (Gelb condition), but not when presented on a Mondrian background, because of the high articulation level provided by this background. Experiment 1 design also included two other backgrounds that produced a partial compression effect. In Experiment 2, two chromatic staircases were used. Employing a naming task, changes in hue perception were only observed for the susceptible staircase. The observed changes were of two types. First, for the full staircase presentations, a Gelb background produced maximum lightness compression (more similarity in the lightness of the staircase stimuli) and, also, a minimum B-B effect (fewer differences in hue). Second, only for the Gelb condition, there were changes in the hue of the lowest luminance staircase stimuli depending on the staircase extension. Results are discussed in the framework of the anchoring theory of lightness perception.